2014
DOI: 10.1253/circj.cj-14-0814
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Its Association With Sudden Cardiac Death

Abstract: 2588CHEN LY et al. Circulation JournalOfficial Journal of the Japanese Circulation Society http://www. j-circ.or.jp are only starting to understand -SCD. We will review the evidence for an independent relationship between AF and SCD in different contexts: recipients of implantable cardioverterdefibrillators (ICDs), patients with MI, HF, or hypertension (HT), and finally, in the general population. We will also examine the determinants of SCD in patients with AF and postulate on the mechanisms underlying this n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 37 publications
0
41
1
Order By: Relevance
“…In addition, the irregular rhythm of AF may lead to short-long-short sequences which are intrinsically proarrhythmic22. Therefore, AF itself may facilitate the induction of VAs and cause SCD23.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the irregular rhythm of AF may lead to short-long-short sequences which are intrinsically proarrhythmic22. Therefore, AF itself may facilitate the induction of VAs and cause SCD23.…”
Section: Discussionmentioning
confidence: 99%
“…SCD is the single most common cause of death among patients with AF, accounting for about a third of all deaths 23, 24, 25, 26. In a recent analysis from the ENGAGE AF‐TIMI 48 trial, the cause for SCD was unknown in most cases and an arrhythmia was documented in only a minority of SCD events (11.5%) 25.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous studies have provided conflicting findings concerning the association of AF and mortality, 3,17-19 recent studies, including a meta-analysis, demonstrated that AF carried adverse prognostic implications for both in-hospital and long-term mortality rates in patients with AMI. 5,6,8,9,20, 21 Rathore et al reported that patients with NOAF during hospitalization had higher in-hospital, 30-day, and 1-year mortality rates compared with those without AF. 5 They showed that the difference in mortality rates between in hemodynamic status may influence the development of AF during AMI.…”
Section: Discussionmentioning
confidence: 99%